Intelligence and state surveillance in modern societies : an international perspective - Lemieux, Frederic (Emerald Publishing Limited, 2019)
Since the dissolution of the Soviet Union in the early 1990's, Western state surveillance and intelligence activities have drastically adapted to new domestic and global challenges. This book examines the evolution of state surveillance in modern societies and provides an international perspective on influential trends affecting these activities.